Epidemiological profile of acute poisoning in children admitted to a tertiary care hospital - M., Mathivanan; K., Vignesh (International Journal of Contemporary Pediatrics, 2019)
Background: Acute poisoning in children is most commonly encountered in day to day practice which contributes a major part of admissions in pediatric intensive units and ward. It is a preventable public health problem. There are limited community based data available because of several reasons including lack of standard case definition, regional variability, poor functioning regulatory and surveillance system. Therefore, authors carried out this study in present set-up. Methods: A prospective observational study carried out at a tertiary care hospital which included all children within the age of 12 years presenting with history and symptoms and signs suggestive of acute poisoning over a period of 1 year after getting consent from parents. Results: Incidence of acute poisoning among children was 4.7%. Maximum cases were in the age group of 1-5 years (79.85%). Among the 278 cases, male children were 154(55.4%) and female were 124(44.6%). Majority of cases were observed in upper lower (43.1%) socio-economic group of Modified Kuppusamy scale. Based on locality, majority of cases were from rural area (66.9%). Accidental poisoning was the most common cause including 88.5% cases. In our study, we found that hydrocarbons were the most common substance of poisoning (58%). The most common clinical presentation in our study was vomiting (24.5%). Conclusions: Incidence of acute poisoning among children is high in our set-up. Lower socio-economic class, rural populations are important epidemiological factors which influences the poisoning event in children.